Book review: the novel “Teluk Alaska” - Wajdi, Majid; Susanto, Budi; Yuniantari, Ni Putu Intan; Nirmala , Ni Kadek Wahyu Dian; Dewi, Ayu Putu Lina Puspita; Kumbhayoni, Putu Diah Keshy; Putri, Kiki Hermalia (Journal of Language, Literature, Social and Cultural Studies, 2023)
The general problem in this study is "How the main character's conflict in the  novel Teluk Alaska is". The specific problems in this review are (1) How is the internal conflict of the main character in the novel Teluk Alaska? (2) What is the external conflict of  the main character in the novel Teluk Alaska (3) How are the efforts to resolve the conflict  of the main character in the novel Teluk Alaska? The general aim of this research is to find out the conflict of the main character in the novel. The specific  objectives of this study are (1) to describe the internal conflict of the main character in the novel (2) to describe the main character's external conflicts in the novel (3) describe efforts to resolve the conflict  of the main character in the novel. The data    source in this study is the novel, which was  published by Coconut Books in 2019 with a total of 408 pages. Based on the results of the analysis of the main character's conflict in the novel with a literary psychology approach, that the conflict of the main character, namely internal  conflict, factors of external conflict, and conflict resolution efforts. The internal conflicts include guilt, buried guilt, shame,  sadness, hatred, and love. External conflicts are  physical conflicts and social conflicts. Meanwhile, conflict resolution efforts are moving against other people and moving to stay away from other people.